Faktor - Faktor yang Mempengaruhi Financial Distress pada Perusahaan Sektor Teknologi - Valensia, Valensia; Wenny, Cherrya Dhia (MDP Student Conference, 2024)
This research aims to find out the influence of capital structure, liquidity and cash flow on financial distress. The research approach uses causal quantitative. The sample was determined using purposive sampling from technology sector companies over 4 periods and 56 data were obtained. The results show that partially, capital structure has a negative influence on financial distress, liquidity has a positive influence on financial distress and cash flow has no influence on financial distress. Simultaneously, capital structure, liquidity and cash flow have an influence on financial distress.